Free Convection Boundary Layer Flow on a Horizontal Circular Cylinder in a Nanofluid with Viscous Dissipation - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohd Zuki, Salleh; Anuar, Ishak (Universiti Kebangsaan Malaysia, 2016)
In this paper, the problem of free convection boundary layer flow on a horizontal circular cylinder in a nanofluid with viscous dissipation and constant wall temperature is investigated. The transformed boundary layer equations are solved numerically using finite difference scheme namely the Keller-box method. Numerical solutions were obtained for the reduced skin friction coefficient, Nusselt number and Sherwood number as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for various values of the Brownian motion parameter, thermophoresis parameter, Lewis number and Eckert number were analyzed and discussed.